2017
DOI: 10.1016/j.landurbplan.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and use of peri-urban green space for inner-city dwellers: A comparative study

Abstract: Peri-urban landscape, space between the rural and urban setting, has generally been seen in planning practice as space in a transient state, likely to be developed in the future. However, research has shown that peri-urban green spaces have increasingly been used for recreational and leisure purposes by urban and rural dwellers. This study aims to explore whether, if urban dwellers' preferred green spaces are large peri-urban semi-natural areas, they will nonetheless be used only infrequently if the accessibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 33 publications
4
62
0
4
Order By: Relevance
“…By applying the Gini coefficient, research has shown that there are disparities in green space arrangement in major German cities. Additionally, solid incongruities identified in green space arrangement at a city level ranged from 2.5 m 2 per capita (city of Schwerin) to 36.3 m 2 (city of Bergisch Gladbach) within a 500 m buffer around the place of home [91]. Discernments of distance to travel were the major obstructions to the frequent use of peri-urban green spaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By applying the Gini coefficient, research has shown that there are disparities in green space arrangement in major German cities. Additionally, solid incongruities identified in green space arrangement at a city level ranged from 2.5 m 2 per capita (city of Schwerin) to 36.3 m 2 (city of Bergisch Gladbach) within a 500 m buffer around the place of home [91]. Discernments of distance to travel were the major obstructions to the frequent use of peri-urban green spaces.…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, modern advancements must include plant life, within the frame of green rooftops, cascading vertical gardens, and verdant dividers. The thrust to "go green" extends to development as well; green building has been obligatory since 2008 [91]. In Marina Bay, all advancements comply with a 100% greenery substitution approach.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale in selecting this particular city as a case study is manifold. The city is acknowledged for its central position within the Slovenian urban system (Nared et al, 2017), its high quality of urban life (Tiran, 2016), diverse urban morphology and urban land use , also as sustainability-oriented, compact and green (Nastran and Green, 2016;Žlender and Ward-Thompson, 2017). The city is also known for its activities in improving conditions for walking, and signing the International Charter for Walking (https://www.walk21.com/charter).…”
Section: Methodsmentioning
confidence: 99%
“…In the early 1990s in Ljubljana, spatial development was neglected because of prioritising macro-economic reforms at the national level. This led to the expansion of a dispersed or scattered residential and retail sprawl (Žlender and Ward Thompson, 2017), explaining the poorer walking accessibility on the outskirts.…”
Section: Walking Accessibility Indicesmentioning
confidence: 99%
“…Agency for environment protection in USA defines these urban heath islands as a phenomenon, which appears when urban areas are warmer than its surroundings [40]. Radiation, thermal, and hydraulic characteristics of materials varies mainly depending of its kind: from materials made of stone, soil, vegetation, or water.…”
Section: Basic Definitions and The Nature Of Phenomenonmentioning
confidence: 99%